Ethical Issues Regarding Neurosurgical Management of Penetrating Brain Injury in the French Armed Forces - Fawaz, Rayan; Fouet, Mathilde; Brenot, Godefroi; Bertani, Antoine; Lamblin, Antoine; Delmas, Jean-Marc (Military medicine, 2024)
ABSTRACT Combat penetrating brain injury (PBI) differs significantly from PBI in civilian environments. Differences include technical factors such as the weapons involved, strained resource environments, and limited medical materials and human resources available. Ethical issues regarding the management of PBI in military settings may occur. This case study examines the case of a 20-year-old member of the French Armed Forces that suffered a penetrating brain injury in a combat situation. The four-quadrant method along with the four principles of medical ethics (respect for autonomy, beneficence, nonmaleficence, and justice) was used to analyze this case and to apply ethics to the practice of military medicine. Nowadays, we possess the medical and surgical resources as well as the aeromedical evacuation capability to save the life of a soldier with a penetrating craniocerebral wound. Nonetheless, the functional outcome of this type of wound places military doctors in an ethical dilemma. The line of conduct and clinical protocol established by the French Medical Health Service is to manage all PBIs when the patient’s life can be saved and to provide all available financial and social support for the rehabilitation of patients and their family.